Decision Support System for Employee Performance Assessment with SAW and TOPSIS Methods - Aditiya Hermawan; A Damiyati (Komunitas Dosen Indonesia, 2020)
Employees are one important factor of a company. That's because many employees play a role in every activity of a company. Therefore, companies must carry out employee evaluation processes to be able to maintain and mature employee performance. In general, the employee assessment process requires a long time and the results obtained are not necessarily accurate. That is because there are many elements that must be assessed and also the calculation process is still done manually. These elements include work performance, honesty, cooperation, obedience, and loyalty. Based on the problem, a decision support system was created that could simplify and speed up the employee evaluation process. The method used is SAW and TOPSIS which can help to provide accurate results because both methods are suitable for processing data with many criteria or elements. To test the system that has been made, the authors conducted the activity of giving a questionnaire conducted or filled out by 15 users. Based on the results of testing and questionnaires that have been distributed and filled out by users, it was found that around 92% of respondents stated that they were very satisfied with the system as a whole. Then based on the data, this decision support system functions well and is beneficial for users because it helps and facilitates the company in the employee appraisal process and also helps employees know their potential.